Antagonism of regulatory ISGs enhances the anti-melanoma efficacy of STING agonists - Filderman, Jessica N.; Taylor, Jennifer L.; Wang, Jianmin; Zhang, Yali; Singh, Prashant; Ross, Mark A.; Watkins, Simon C.; Nedal Al Bzour, Ayah; Karapetyan, Lilit; Kalinski, Pawel; Storkus, Walter J. (Frontiers in Immunology, 2024)
Background: Stimulator of Interferon Genes (STING) is a dsDNA sensor that triggers type I inflammatory responses. Recent data from our group and others support the therapeutic efficacy of STING agonists applied intratumorally or systemically in a range of murine tumor models, with treatment benefits associated with tumor vascular normalization and improved immune cell recruitment and function within the tumor microenvironment (TME). However, such interventions are rarely curative and STING agonism coordinately upregulates expression of immunoregulatory interferon-stimulated genes (ISGs) including Arg2, Cox2, Isg15, Nos2, and Pdl1 that may limit treatment benefits. We hypothesized that combined treatment of melanoma-bearing mice with STING agonist ADU-S100 together with antagonists of regulatory ISGs would result in improved control of tumor growth vs. treatment with ADU-S100 alone. Methods: Mice bearing either B16 (BRAF WT PTEN WT ) or BPR20 (BRAF V600E PTEN -/-) melanomas were treated with STING agonist ADU-S100 plus various inhibitors of ARG2, COX2, NOS2, PD-L1, or ISG15. Tumor growth control and changes in the TME were evaluated for combination treatment vs ADU-S100 monotherapy by tumor area measurements and flow cytometry/transcriptional profiling, respectively. Results: In the B16 melanoma model, we noted improved antitumor efficacy only when ADU-S100 was combined with neutralizing/blocking antibodies against PD-L1 or ISG15, but not inhibitors of ARG2, COX2, or NOS2. Conversely, in the BPR20 melanoma model, improved tumor growth control vs. ADU-S100 monotherapy was only observed when combining ADU-S100 with ARG2i, COX2i, and NOS2i, but not anti-PD-L1 or anti-ISG15. Immune changes in the TME associated with improved treatment outcomes were subtle but included increases in proinflammatory innate immune cells and activated CD8 + CD69 + T cells and varied between the two tumor models. Conclusions: These data suggest contextual differences in the relative contributions of individual regulatory ISGs that serve to operationally limit the anti-tumor efficacy of STING agonists which should be considered in future design of novel combination protocols for optimal treatment benefit.